2000
DOI: 10.1046/j.1365-2702.2000.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Men living with diabetes: minimizing the intrusiveness of the disease

Abstract: In this paper we present the findings from the second of four Participatory Action Research (PAR) groups with men and women who have been diagnosed with type two diabetes. The findings of the men's group are reported here. People who have received a diagnosis of diabetes must immediately absorb a great deal of information about how to control their diabetes, care for themselves and make lifestyle changes. In this study, we have asked men about this transition and about what it is like to live with diabetes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 19 publications
7
48
2
Order By: Relevance
“…Rather, it refers to men's attempts to control the presence of diabetes in their lives -by ignoring it to pursue personal goals such as work, or attending to it in order to achieve the goals of 'taking care of others'. Koch et al (2000) saw the experimentation with doctor's recommendations by men with diabetes as a means to maintain control and find a personalised 'fit' for diabetes in their lives. The same efforts to personalise the care regimen have been seen in this study as doctors recommendations were often taken into consideration but ultimately each participant pursued a system of 'best fit'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it refers to men's attempts to control the presence of diabetes in their lives -by ignoring it to pursue personal goals such as work, or attending to it in order to achieve the goals of 'taking care of others'. Koch et al (2000) saw the experimentation with doctor's recommendations by men with diabetes as a means to maintain control and find a personalised 'fit' for diabetes in their lives. The same efforts to personalise the care regimen have been seen in this study as doctors recommendations were often taken into consideration but ultimately each participant pursued a system of 'best fit'.…”
Section: Discussionmentioning
confidence: 99%
“…Bacon et al, 2002;Corona et al, 2004;and Jowett, Peel, & Shaw, 2012). Other research has examined the variations in health beliefs amongst men of different ethnic origins (Hjelm, Bard, Nyber & Apelqvist, 2005) and the way men incorporate diabetes into their lives through 'normalisation' (Koch, Kralik, & Taylor, 2000;Peyrot, McMurray, & Hedges, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have studied men and women separately and found dissimilarities in life modes and thus, risk perceptions [11, 12] and health-related behaviour [13, 14]. Women were more caring and nurturing and had higher risk awareness than men who were more ego-oriented and willing to take risks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, women perceived diabetes mellitus as intrusive and feared its complications why their daily lives became stressful, watchful and restricted [13]. Men on the other hand saw diabetes as part of their life, tried to limit its restrictions and thus, described a positive impact of the disease on their life-style and believed the complications meant taking better care of themselves [14]. Comparisons of men of different origin, Arabs, ex-Yugoslavians and Swedes, showed that of importance for health were to be gainfully employed, economically independent and able to retain sexual function [15].…”
Section: Introductionmentioning
confidence: 99%
“…14 Similar to that reported elsewhere, women reported a lower QOL. 15 This may be that men manage their life with diabetes by minimising the intrusiveness of the disease, considering it part of life and not as an illness, 16 and therefore their QOL is less affected by it. Knowledge increased at a group level which supports the usefulness of attendance at the programme.…”
Section: Discussionmentioning
confidence: 99%